Néhány adat a történelmi Dési, Széki és a Görgényi református egyházmegyék orgonáiról - Dávid SIPOS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2017)
A Few Curiosities About The History of The Organs in The Historical Reformed Dioceses of Dej, Sic and Gurghiu.